EVALUASI PERILAKU ANTROPOGENIK DALAM PENGGUNAAN KEMASAN PLASTIK: STUDI KASUS SOSIO-EKOLOGIS PADA KOMUNITAS PERIKANAN KABUPATEN ACEH BARAT - Zuriat, Zuriat; Zuraidah, Syarifah; Amarullah, T.; Ulfia, Ulfia; Syafitri, Rina (JURNAL PERIKANAN TROPIS, 2025)
Coastal communities in Indonesia especially West Aceh face a growing challenge from marine plastic pollution from Fishery Port. This study addresses this issue by examining the understanding of local fisheries stakeholders at two key ports in the region. This study aims to assess the level of understanding among fisheries stakeholders regarding plastic pollution at the Ujong Baroh Fish Landing Port (PPI) in Johan Pahlawan Subdistrict and the fish market located at Ujong Karang Public Port in Meulaboh City. A quantitative descriptive survey approach was employed, with data collected through structured questionnaires administered to 40 respondents comprising fishermen, marine supply providers, and fish traders. The instrument utilized a 5-point Likert scale to measure respondents’ perceptions. Data were analyzed descriptively using frequency distribution and percentage calculations. Findings reveal that the majority of fisheries stakeholders demonstrate a moderate level of understanding, with 57% acknowledging the adverse impacts of plastic waste on marine ecosystems and the surrounding environment. These results suggest an urgent need for enhanced environmental education and outreach initiatives led by port authorities to improve awareness and promote sustainable practices among local fisheries communities.